2020
DOI: 10.12968/bjcn.2020.25.9.438
|View full text |Cite
|
Sign up to set email alerts
|

Effective communication between nurses and patients: an evolutionary concept analysis

Abstract: Communication can be considered as the basis of the nurse-patient relationship and is an essential element in building trust and comfort in nursing care. Effective communication is a fundamental but complex concept in nursing practice. This concept analysis aims to clarify effective communication and its impact on patient care using Rodgers's (1989) evolutionary framework of concept analysis. Effective communication between nurses and patients is presented along with surrogate terms, attributes, antecedents, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…Consistent with this finding, Chapman et al also stated that due to the special condition and emotional and psychological instability of patients and families, as well as pressures from various sources, cancer patients may show aggressive behaviors towards nurses (17). Afriyie also acknowledged that the observance of boundaries and intimacy and preserving privacy and hierarchy in relationships while performing professional duties are pillars in organizational communications (18).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with this finding, Chapman et al also stated that due to the special condition and emotional and psychological instability of patients and families, as well as pressures from various sources, cancer patients may show aggressive behaviors towards nurses (17). Afriyie also acknowledged that the observance of boundaries and intimacy and preserving privacy and hierarchy in relationships while performing professional duties are pillars in organizational communications (18).…”
Section: Discussionmentioning
confidence: 87%
“…The category of professional communications' threats consisted of the subcategories of challenges in the nursedoctor relationship, some physicians neglecting nurses while visiting patients, and tensions in the relationship between nurses and supervisors. Afriyie (18) and Mahdizadeh et al (20), who investigated nurses' perceptions regarding intra-professional communications reported that the most critical problem in this area was nurses being subjected to non-respectful behaviors by physicians. Physicians' lack of knowledge of the nursing profession (21) and holding clinical rounds without the presence of nurses (15) have been reported as the factors compromising the nursephysician relationship, which were also noted among the experiences of our participants.…”
Section: Discussionmentioning
confidence: 99%
“…Support such as caring and education can be provided within effective nurse-to-family communication. 33…”
Section: Family Caregiver and Patient Characteristics With Uncertaint...mentioning
confidence: 99%
“…ENs also emphasized the need for communication techniques tailored to patients’ different diseases and symptoms. Thus, effective communication between ED nurses and patients is crucial for realizing patient-centered care [36] and achieving personalized emergency nursing care. Moreover, it is essential to establish protocol-based communication strategies specific to patients’ diseases and symptoms, as nurses cannot apply a uniform strategy for all ED patients.…”
Section: Continuous Endeavors For Improved Communicationmentioning
confidence: 99%